The effectiveness of group counseling with the keeping diaries of events technique in reducing excessive dating app use among adolescents experiencing romantic breakups - Wulandari, Sri Ugika; Harahap, Adhe Chita Putri (Institute of Computer Science (IOCS), 2025)
This study aimed to determine the effectiveness of group counseling using the Keeping Diaries of Events technique in reducing excessive dating app use among adolescents after experiencing a romantic breakup. The research employed a quantitative approach with a One-Group Pretest–Posttest design. Five participants were selected through purposive sampling based on predetermined criteria. Data were collected using a Likert-scale instrument, diary documentation, and observation sheets. The Wilcoxon Signed Rank Test was used as the inferential analysis technique to evaluate differences between pretest and posttest scores. The results showed a significance value of 0.043, indicating a meaningful decrease in excessive dating app use after the intervention. These findings suggest that group counseling combined with diary-based self-monitoring contributes to improved emotional awareness and behavioral regulation among adolescents following breakup-related distress.